Enhancing Athletes' Foot Stability: A Comparative Analysis of Gluteus Maximus and Gluteus Medius Muscle Strengthening Effects on Navicular Drop, Balance, and Foot Posture Index in Over-Pronated Foot - Charu Chhabra; Uma Raghav; Bharti Sharma; Harsirjan Kaur (Pamukkale University, 2024)
This study aimed to determine the effectiveness of gluteus maximus versus gluteus medius muscle strengthening exercises on the navicular drop (ND), balance, and foot posture index (FPI 6) among athletes with over-pronated feet. A pre-post experimental study design with a total of 54 athletes with bilateral over-pronated feet were randomly assigned into group A (n=18), group B (n=18), and group C (n=18). Medial longitudinal arch height (MLA) was assessed with the Navicular Drop Test, the static and dynamic balance was determined with the stork stance test (SST) and modified Star Excursion Balance Test, and Foot Posture was assessed with Foot Posture Index 6. Multivariate Repeated measures ANOVA was used to analyze the effects of gluteus maximus versus gluteus medius muscle strengthening and short foot exercises. At four weeks, the gluteus medius along with short foot exercises (group B) showed significantly less ND and FPI 6 while showing more excellent SST and modified SEBT than the gluteus maximus muscle strengthening along with short foot exercises (group A) and control group (group C). These results suggest that adding gluteus medius muscle strengthening exercises to short foot exercises (SFE) was more effective in supporting the medial longitudinal arch and improving balance than performing SFE alone.